Preservation of red meat with natural antimicrobial peptides produced by lactic acid bacteria - Kohrs, Gertruida Ansia (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScVoedselwet)--University of Stellenbosch, 2004.